LEGAL POLICY ON EXHIBITIONISM THROUGH VIDEO CALL-BASED SOCIAL MEDIA REVIEWED FROM THE INFORMATION AND ELECTRONIC TRANSACTIONS (IET) LAW - Suarsika, I Komang; Wiratny, Ni Ketut; Sihotang, Erikson (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
The advancement of information technology has significantly impacted society, transforming conventional crimes into cybercrimes using computers and the internet. One such example is exhibitionism via video call-based social media. This act is not yet specifically addressed in the Information and Electronic Transactions (IET) Law. Applying Article 27 Paragraph (1) of the IET Law, which deals with indecent acts, does not cover this scenario as it lacks the "known to the public" element, creating a legal gap. Consequently, two issues arise: the legal regulation of exhibitionism in Indonesia and the legal policy considerations for exhibitionism through video call-based social media under the IET Law. This normative research employs legislative, conceptual, and historical approaches, drawing from primary, secondary, and tertiary legal materials collected through library research. The materials are analyzed using descriptive, systematization, construction, argumentation, and evaluation techniques. To address this legal gap, policy reforms in criminal law are necessary. Amending Article 27 Paragraph (1) of the IET Law to include "to another person without the consent or desire of that person" is essential. This amendment would allow the prosecution of exhibitionism via video call-based social media, ensuring legal certainty and protection for victims, particularly women and children.